3,4-Dihydroxyphenylacetaldehyde Is More Efficient than Dopamine in Oligomerizing and Quinonizing α-Synuclein - Jinsmaa, Yunden (J Pharmacol Exp Ther, 2020)
Lewy body diseases such as Parkinson’s disease involve intraneuronal deposition of the protein α-synuclein (AS) and depletion of nigrostriatal dopamine (DA). Interactions of AS with DA oxidation products may link these neurohistopathologic and neurochemical abnormalities via two potential pathways: spontaneous oxidation of DA to dopamine-quinone and enzymatic oxidation of DA catalyzed by monoamine oxidase to form 3,4-dihydroxyphenylacetaldehyde (DOPAL), which is then oxidized to DOPAL-Q. We compared these two pathways in terms of the ability of DA and DOPAL to modify AS. DOPAL was far more potent than DA both in oligomerizing and forming quinone-protein adducts with (quinonizing) AS. The DOPAL-induced protein modifications were enhanced similarly by pro-oxidation with Cu(II) or tyrosinase and inhibited similarly by antioxidation with N-acetylcysteine. Dopamine oxidation evoked by Cu(II) or tyrosinase did not quinonize AS. In cultured MO3.13 human oligodendrocytes DOPAL resulted in the formation of numerous intracellular quinoproteins that were visualized by near-infrared spectroscopy. We conclude that of the two routes by which oxidation of DA modifies AS and other proteins the route via DOPAL is more prominent. The results support developing experimental therapeutic strategies that might mitigate deleterious modifications of proteins such as AS in Lewy body diseases by targeting DOPAL formation and oxidation. SIGNIFICANCE STATEMENT: Interactions of the protein α-synuclein with products of dopamine oxidation in the neuronal cytoplasm may link two hallmark abnormalities of Parkinson disease: Lewy bodies (which contain abundant AS) and nigrostriatal DA depletion (which produces the characteristic movement disorder). Of the two potential routes by which DA oxidation may alter AS and other proteins, the route via the autotoxic catecholaldehyde 3,4-dihydroxyphenylacetaldehyde is more prominent; the results support experimental therapeutic strategies targeting DOPAL formation and DOPAL-induced protein modifications.